Pemikiran Pendidikan Pluralisme KH. Abdurrahman Wahid - Sarno Hanipudin; Afif Anasrulloh Alhaq (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2017)
Indonesia is a pluralistic, diverse country, language and even religion. Indonesia is a "vulnerable" country to conflict because of pluralism. The conflict is very likely that the understanding of pluralism has not been built strongly, the SARA issue ahead of national political contestation is expected to continue to grow rooted In line with the dynamics that occurred. This paper tries to show Gusdur's thoughts on pluralism, as a religious and political figure, Gusdur's thought is considered as a reference to deepen and strengthen the education of pluralism in Indonesia.